Electrocardiographic and blood pressure effects of energy drinks and Panax ginseng in healthy volunteers: A randomized clinical trial. (1st September 2016) - Shah, Sachin A.; Occiano, Andrew; Nguyen, Tinh An; Chan, Amanda; Sky, Joseph C.; Bhattacharyya, Mouchumi; O'Dell, Kate M.; Shek, Allen; Nguyen, Nancy N.
Abstract: Background: Energy drink usage has been linked to emergency room visits and deaths. The objective of the study is to assess the electrocardiographic and blood pressure effects of energy drinks, Panax ginseng and placebo in healthy individuals. Methods: This was a randomized, double blinded, placebo controlled, crossover study. Young healthy volunteers with no comorbid conditions consumed 32 oz of an energy drink, control drink with 800 mg of Panax ginseng or matching placebo-control drink over 45 min. Primary endpoints were QTc interval and systolic blood pressure. Secondary endpoints included QT interval, PR interval, QRS duration, heart rate, and diastolic blood pressure. All endpoints were assessed at baseline, 1, 2, 3.5, and 5.5 h. Results: A significant increase in QTc interval 2 h post energy drink consumption was evident when compared to placebo (3.37 ± 10.7 ms and − 3.19 ± 11.8 ms respectively; p = 0.030). Similarly, systolic blood pressure 2 h post energy drink consumption increased when compared to placebo (2.00 ± 6.37 mm Hg and − 2.67 ± 5.83 mm Hg respectively; p = 0.014). The PR interval significantly reduced over a 2 h period post energy drink use in a clinically non-meaningful manner. Heart rate at 2 h was not significantly higher in the energy drink group when compared to others. The QT interval, QRS interval and diastolic blood pressure were not impacted at any time point. Conclusions: Certain energy drinks consumed at a high volume significantly increase the QTc interval and systolic blood pressure by over 6 ms and 4 mm Hg respectively. Panax ginseng does not have a significant impact on ECG or blood pressure parameters.